Tanaidacea (Crustacea) of the Northeast Atlantic: non-filiform species of Anarthruridae Lang from the Atlantic Margin - Bird, Graham (Zootaxa, 2004)
Anarthrurid tanaidaceans are common in the bathyal zone west of the British Isles and their identification has been difficult. The complex history of the taxonomy and classification of the Family Anarthruridae Lang is summarised and H.J. Hansen s Leptognathia group d from the Ingolf expeditions is transferred to the Anarthruridae. Three known species are re-described (Anarthrurasimplex, Leptognathia latiremis, and L. glacialis). In addition, five new genera are erected and five new species described. A key to their identification is given. Zoogeographic patterns indicate a cold-water fauna north of the Faeroes and Iceland and a separate Atlantic Deep Sea fauna along the Hebrides-Porcupine-Biscay slope.